Kontekstualisasi Teologis Sakramen Tobat dalam Tradisi Sob Lor pada Masyarakat Kei Provinsi Maluku - Bernard Antonius Rahawarin; Fabianus Selatang; Ignasius S.S. Refo (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2021)
Contextualization of theology is no longer optional but is the essence of theology itself. One of the contextualization spaces is the cultural tradition of the community. In the Kei community in Maluku Province, various traditions contain theological elements that form theological contextualization. This study aims to find the theological aspects of the Sacrament of Penance in a Kei cultural practice known as Sob Lor. The method used in this study is a qualitative-descriptive method with a semiotic approach. The data described were collected through literature review and in-depth interviews at Kei. This study succeeded in finding a meeting point between the sacrament of penance and the Sob Lor tradition in the Kei community. The sacrament of penance aims to improve the sinner's relationship with the Church due to sin. At the same time, the Sob Lor tradition or village cleansing rite is primarily a cleansing due to violations of customary law. This study found four theological elements of the Sacrament of Penance contained in the Sob Lor ritual: Allah, Sin, the conditions of forgiveness, and the results of participation in the rite. These four things meet each other between the theological concept of the sacrament of penance with the Sob Lor tradition. Thus, the meeting point of the Catholic faith tradition and the Kei culture can be material to deepen and increase the Catholic faith.